Specific phytochemicals in floral nectar up‐regulate genes involved in longevity regulation and xenobiotic metabolism, extending mosquito life span. Issue 12 (25th May 2021) - Njoroge, Teresia M.; Calla, Bernarda; Berenbaum, May R.; Stone, Christopher M.
Abstract: During nectar feeding, mosquitoes ingest a plethora of phytochemicals present in nectar. The ecological and physiological impacts of these ingested phytochemicals on the disease vectors are poorly understood. In this study, we evaluated the effects of three nectar phytochemicals‐‐ caffeine, p ‐coumaric acid, and quercetin‐‐on longevity, fecundity, and sugar‐feeding behavior of the Asian tiger mosquito ( Aedes albopictus) . Adult females of Ae .  albopictus were provided continuous access to 10% sucrose supplemented with one of the three phytochemicals and their fecundity, longevity, and the amount of sucrose consumed determined. Transcriptome response of Ae .  albopictus females to p ‐coumaric acid and quercetin was also evaluated. Dietary quercetin and p ‐coumaric acid enhanced the longevity of female Ae .  albopictus, while caffeine resulted in reduced sugar consumption and enhanced fecundity of gravid females. RNA‐seq analyses identified 237 genes that were differentially expressed (DE) in mosquitoes consuming p ‐coumaric acid or quercetin relative to mosquitoes consuming an unamended sucrose solution diet. Among the DE genes, several encoding antioxidant enzymes, cytochrome P450s, and heat shock proteins were upregulated, whereas histones were downregulated. Overall, our findings show that consuming certain nectar phytochemicals can enhance adult longevity of female Asian tiger mosquitoes, apparently by differentially regulating the expression level of genes involved in longevity and xenobiotic metabolism; this has potential impacts not only on life span but also on vectorial capacity and insecticide resistance. Abstract : The study investigated the effects of nectar phytochemicals caffeine, p ‐coumaric acid, and quercetin on longevity, fecundity, and sugar‐feeding behavior of female Aedes albopictus . Additionally, we did a whole‐transcriptome analysis of female Ae .  albopictus consuming sucrose diets supplemented with p ‐coumaric acid or quercetin to characterize their transcriptional profile. Quercetin and p ‐coumaric acid significantly enhanced the longevity of the mosquitoes while caffeine consumption resulted in reduced sugar feeding and enhanced fecundity. Dietary p ‐coumaric acid or quercetin led to a change in expression of genes associated with longevity regulation (superoxidase dismutase, heat shock proteins, and histones) and xenobiotic metabolism (P450s and other enzymes involved in degradation of toxins).